An Analysis of Meaning in Language Style’s on Sunday School Children’s Song - Kapoh, Elviranda Januaro Rezika; Andries , Fivy A.; Posumah, Jenie (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2024)
The aim of this research are to make a real contribution to the field of semantic studies by providing a deeper understanding of how meaning is constructed through language styles in Sunday school children's song lyrics. This research was delimited to seven Sunday School children's songs. Tarigan's (2009) theory with four language style groups, namely comparative language style, conflicting language style, linking language style and repetition language style, was used to analyze language style. Meanwhile, the theory from Mansore Pateda (2001) is used to analyze meaning, namely, lexical meaning, grammatical meaning, contextual meaning, referential meaning, denotative meaning, connotative meaning and cognitive meaning. In conducting this research the researcher used a qualitative descriptive method. Data collection was carried out through watching YouTube videos and recording song lyrics. The steps of Miles and Huberman (1994) were used to determine the results of data analysis, namely data reduction, data presentation, and conclusions. The research results found that there were 40 language styles which were classified into 13 types of language styles, namely Comparative language styles: Pleonasm, Metaphor, Personification, Antithesis; Conflicting Styles: Hyperbole, apostrophe; Connecting language styles: Parallelism, Asyndeton; Repetitive language styles: Alliteration, Tautotes, Anaphora, Assonance, Epizeuksis. And 21 data of meanings wich are classified in 2 types of meaning, namely Connotative Meaning and Denotative Meaning. The results of the research are expected to be useful for readers as a reference for understanding more deeply how language styles communicate meaning and can help create an interesting and effective curriculum. This can enrich academic literature on the semantic analysis of religious texts.